Zimbabwe : Staff Report for the 2016 Article IV Consultation and the Third Review of the Staff-Monitored Program-Press Release; Staff Report; and Statement by the Executive Director for Zimbabwe. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses recent developments, outlook, and risks related to the economy of Zimbabwe. Zimbabwe's economic difficulties have deepened. GDP growth slowed significantly to 1.1 percent in 2015, mainly because of the impact of adverse weather conditions on agricultural output, and power generation. The current account balance improved in 2015, because of lower prices for oil imports, subdued economic activity, and fiscal consolidation efforts. Fiscal performance in 2015 was better than programmed, despite the adverse macroeconomic environment. Despite spending pressures to mitigate the impact of the drought, the authorities remain committed to fiscal discipline; they target a primary cash deficit of 0.2 percent of GDP for 2016.